Rethinking cultural appropriation in YA literature through Sámi and arctic pedagogies - Manderstedt, L. (Lena); Palo, A. (Annbritt); Kokkola, L. (Lydia) (Springer Nature, 2020)
Abstract This article highlights cultural appropriation in the literary representation of the Sámi (the indigenous people of the European Arctic) in two Swedish YA series: the Soppero quartet by the Sámi author Ann-Helén Laestadius, and the Idijärvi trilogy by Charlotte Cederlund, a non-Sámi writer. Despite their different origins, the series are more similar than different in their portrayal of most aspects of Sámi-Swedish relations. The discussion of cultural appropriations in the production and marketing of the series is contextualized within broader concerns, especially in relation to Sámi and Arctic pedagogies. We begin by noting that both protagonists are initially marginalized in both the Swedish and the Sámi contexts, but their ways of gaining agency are markedly different. Connecting these points to the authors’ ethnic affiliation does not produce useful knowledge or knowledge that can be shared, two hallmarks of Sámi and Arctic pedagogies. We argue that Sámi and Arctic pedagogies provide more relevant tools for discussing cultural appropriation in relation to literature from the region than the currently dominant models derived from Anglophone contexts. Through our pedagogically inspired analyses of voice and agency in the two series, we endeavour to create a Nordic ethics of appropriation.